2022
DOI: 10.1101/2022.05.04.490632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping the T cell repertoire to a complex gut bacterial community

Abstract: Certain bacterial strains from the microbiome induce a potent, antigen-specific T cell response. However, the specificity of microbiome-induced T cells has not been explored at the strain level across the gut community. Here, we colonize germ-free mice with a complex defined community (97 or 112 bacterial strains) and profile T cell responses to each strain individually. Unexpectedly, the pattern of T cell responses suggests that many T cells in the gut repertoire recognize multiple bacterial strains from the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…s3c-f )—is not only composed of repeats but also forms ordered aggregates 44 , creating even more crosslinking potential. The B domain is widely conserved among Gram-positive bacteria 45 and is under selective pressure during an infection 46 , reminiscent of the conserved epitopes recognized by commensal specific CD4 + T cells in the intestine 5,11 and suggesting that pre-emptive immune responses may protect against a broader set of strains than the elicitor. Immune recognition of repeat sequences in sortase substrates—in mice and humans 47 —may be more general than was previously known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…s3c-f )—is not only composed of repeats but also forms ordered aggregates 44 , creating even more crosslinking potential. The B domain is widely conserved among Gram-positive bacteria 45 and is under selective pressure during an infection 46 , reminiscent of the conserved epitopes recognized by commensal specific CD4 + T cells in the intestine 5,11 and suggesting that pre-emptive immune responses may protect against a broader set of strains than the elicitor. Immune recognition of repeat sequences in sortase substrates—in mice and humans 47 —may be more general than was previously known.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, the adaptive immune response to microbial colonists is puzzling. Three of its features are notable: its tone is determined by the microbial elicitor [1][2][3][4] ; it is antigen-specific [5][6][7][8][9][10][11] , just like an anti-pathogen response; and it is pre-emptive-it occurs in the absence of infection or inflammation, across an intact barrier. Given that microbial residents of the gut, skin, and nasal cavity are thought to be generally mutualistic, what is the purpose of this response?…”
Section: Introductionmentioning
confidence: 99%
“…Although antigen-specific interactions between gut-derived bacterial strains and mucosal Th17 cells have been described (Britton et al, 2020; Goto et al, 2014; Ivanov et al, 2009; Viladomiu et al, 2017; Xu et al, 2018), it is not clear how microbe-specific T cells respond to antigens across the phylogenetic space of the microbiome. A recent study found that multiple TCR clonotypes sampled against a defined microbial community react against an epitope widely conserved among Firmicutes (Nagashima et al, 2022). We observe that T cells primed with some microbial strains can similarly cross-react with related species.…”
Section: Discussionmentioning
confidence: 99%
“…However, identifying the bacterial strains within a complex human microbiota that shape intestinal T cell phenotypes has proven challenging. Besides several limited examples, we do not understand the molecular mechanisms and the microbial signals that lead to specific T cell responses in the gut (Ansaldo et al, 2019; Ivanov et al, 2009; Nagashima et al, 2022; Tan et al, 2016). Efforts to parse microbiota-dependent immune phenotypes have either used time-intensive methods or relied upon trial-and-error in vivo experimentation (Atarashi et al, 2015, 2011; Britton et al, 2020; Britton and Faith, 2021; Faith et al, 2014; Geva-Zatorsky et al, 2017; Surana and Kasper, 2017; Viladomiu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, identifying the bacterial strains within a complex human microbiota that shape intestinal T cell phenotypes has proven challenging. Besides several limited examples, we do not understand the molecular mechanisms and the microbial signals that lead to specific T cell responses in the gut ( 10 13 ). Efforts to parse microbiota-dependent immune phenotypes have either used time-intensive methods or relied upon trial-and-error in vivo experimentation ( 2 – 5 , 14 17 ).…”
mentioning
confidence: 99%